2022
DOI: 10.1007/s12678-021-00704-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Ivermectin Used for the Treatment of COVID-19 with Glutardialdehyde-Modified Glassy Carbon Electrode

Abstract: Graphical abstract In this study, the surface of the glassy carbon electrode was modified with glutardialdehyde. The modified glassy carbon electrode showed electrocatalytic activity against ivermectin. The glassy carbon electrode modified with glutardialdehyde showed high sensitivity, selectivity, and stability in the determination of ivermectin. The peak current of glutardialdehyde oxidation obtained by differential pulse voltammetry decreased inversely with the ivermectin concentration. Ivermecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The repeatability of the peak potential (RSD %) and the peak current (RSD %) between days were found to be 0.3 and 4.41, respectively. It was found that the RSD % value of the peak potential and peak current of the CuO‐GA 2 /BDDE within the same day and over the course of different days was less than 5 %, which indicates good electrode repeatability [22,44,45] …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The repeatability of the peak potential (RSD %) and the peak current (RSD %) between days were found to be 0.3 and 4.41, respectively. It was found that the RSD % value of the peak potential and peak current of the CuO‐GA 2 /BDDE within the same day and over the course of different days was less than 5 %, which indicates good electrode repeatability [22,44,45] …”
Section: Resultsmentioning
confidence: 98%
“…It was found that the RSD % value of the peak potential and peak current of the CuO-GA 2 /BDDE within the same day and over the course of different days was less than 5 %, which indicates good electrode repeatability. [22,44,45] The method used to determine the DPV of vitamin B6 on the CuO-GA 2 /BDDE (pulse time: 10 ms, a pulse amplitude: 200 mV • s À 1 , Estep: 2 mV • s À 1 , and v: 50 mVs À 1 ). Comparison of the linear range and limits of detection (LOD) of different electrodes and methods used for the electroanalysisof vitamin B6 is given Table 1.…”
Section: Voltammetricdetermination Of Vitamin B6 On Cuo-ga 2 / Bddele...mentioning
confidence: 99%
See 2 more Smart Citations
“…Electroanalytical methods present special features, such as miniaturized detection systems, portable instrumentation, simple operation, and low generation of residues, which make them as a powerful strategy for IVM determination. The literature mainly reports the use of modified electrodes for IVM determination in several samples, especially glassy carbon disc electrodes, which were modified with reduced graphene doped with silver nanoparticles decorated B and S heteroatoms, 9 glutaraldehyde 10 and β-cyclodextrin/graphene. 11 Alternatively, a boron-doped diamond electrode coupled with Flow Injection Analysis (FIA) system was also reported for IVM determination.…”
Section: Introductionmentioning
confidence: 99%